REALIZING ENVIRONMENTAL-ORIENTED ISLAMIC EDUCATION BASED ON THE VALUES IN THE QUR’AN - Annisa Mayasari (An Natiq, 2023)
The environment and humans are two inseparable things, both are interconnected and influence each other. The environment as a unitary space with all objects, power, circumstances, and living things, has organized life for humans and provided all the necessities of life. Meanwhile, humans as leaders on earth (khalifah fil ardh) have a role to maintain and preserve the surrounding environment. However, human attitudes and behavior often cause environmental damage and natural disasters. Human greed to exploit nature has caused various environmental problems on earth. The presence of Islam through the Qur'an helps humans to carry out their duties in maintaining environmental sustainability and harmony and also solving any existing problems. Through the Qur'an, Allah SWT. has provided spiritual information to humans to be friendly and care for the environment. The content of values ​​​​in the Qur'an about the environment can be a guide for realizing Islamic education with an environmental perspective. Environmental education is an effort towards a balanced life between humans and their environment, which is characterized by cultivating a livable and sustainable ecosystem. This research focuses on the study of the efforts to realize environmentally Islamic education based on the values ​​​​in the Qur'an. The method used in this research is library research. From the results of this study, it was obtained a study of environmental Islamic education and its values, the environment in the view of the Qur'an, as well as steps to realize environmental Islamic education.